(untitled) (Eurasian Journal of Philology Science and Education, 2025)
The semantics of zoomorphic phrases in Turkic languages are considered in the article. The semantics of phrases containing zoomorphic nominations, which are among universal metaphorical models, are analyzed in the article. In the course of the analysis, the spread of stereotypical and national characteristics, the adoption of animal images in person descriptions, and the comparative study in Turkic languages are brought to the fore. The article aims to analyze common zoomorphic phrasemes in Turkic languages in a cognitive model. Among the research methods of the article, we refer to the method of structural-semantic modeling: it is used to determine the preservation of the given general Turkic phraseological fund in modern Turkic languages and its position in the lexical fund. The novelty of the research is that zoomorphic phrases, which inform about the spiritual and material culture of the Turkic peoples, are being studied for the first time as defining units of the national cultural character of the Turks as a result of the research revealed differences in zoomorphic phrases, which summarized imagery, conceptual, and value criteria depending on lingua-creative, pragmatic, and lingua-cultural factors. Keywords: phraseology, animalistic phraseology, comparative-historical study, semantics, phraseological dictionary, lexicon-phraseological fund.